2020
DOI: 10.3390/bioengineering7030093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lasers and Their Delivery Characteristics on Machined and Micro-Roughened Titanium Dental Implant Surfaces

Abstract: The aim of the study was to investigate the effects of neodymium: yttrium aluminium garnet (Nd:YAG) (1064 nm) and erbium: yttrium aluminium garnet (Er:YAG) (2940 nm) laser energy on titanium when delivered with conventional optics (focusing handpieces or plain ended optical fibres) or with a conical tip. Machined and micro-roughened implant discs were subjected to laser irradiation under a variety of energy settings either dry (without water) or wet (with water). Samples were scanned using a 3D non-contact las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 41 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…When multiple Nd:YAG laser pulses are delivered onto the same site, extensive changes to the titanium surface will result. Fenelon et al in 2020 showed this effect for both machined and rough surface titanium samples irradiated with plain fibre tips and documented severe surface modifications, which increased in severity with increasing pulse energy [63]. The nature of such effects can be documented using measurements of surface roughness, as well as 3D imagery (Fig.…”
Section: Nd:yag Lasermentioning
confidence: 96%
See 3 more Smart Citations
“…When multiple Nd:YAG laser pulses are delivered onto the same site, extensive changes to the titanium surface will result. Fenelon et al in 2020 showed this effect for both machined and rough surface titanium samples irradiated with plain fibre tips and documented severe surface modifications, which increased in severity with increasing pulse energy [63]. The nature of such effects can be documented using measurements of surface roughness, as well as 3D imagery (Fig.…”
Section: Nd:yag Lasermentioning
confidence: 96%
“…600 mJ/pulse) could influence machined titanium surfaces, causing roughening of the surface, with a complex pattern of peaks and troughs. Rough implant surfaces with micro and nano-scale features may be more prone to the absorption of laser energy, putting them more at risk of unintended modification of the surface at lower power settings [63]. On many occasions, it is impossible to completely remove the biofilm without causing surface alterations [64].…”
Section: Erbium Lasersmentioning
confidence: 99%
See 2 more Smart Citations
“…Such pulse durations are between one million and one billion times longer than those in the picosecond and femtosecond range used by USP lasers (40). Their effect on dental hard tissues is thermo-mechanical in nature, and they have limited ability to ablate metals and ceramics (42).…”
Section: Development Of Ultrashort Pulse Laser Dentistrymentioning
confidence: 99%